Proteolytic hydrolysis and purification of the LRP/alfa-2-macroglobulin receptor domain from ?-macroglobulins (2007)
A new, easier and efficient purification method, using Sephacryl and DEAE-Sephacel, of the C-terminal fragment of two ?-macroglobulins, ?2-M and PZP, is presented. Two larger peptides were identified for each protein as the C-terminal fragment, with molecular weights of ?30 kDa and the N-terminal sequences were determined to be SSTQDTV for ?2-M and VALHLS for PZP. The smaller peptides with molecular weights of 18 kDa correspond to a shorter C-terminal sequence of these proteins, and they were determined to be EEFPFA for ?2-M and ALKVQTV for PZP, with no interfering sequences detected. The results confirmed the discriminatory capacity of the purification procedure and the purity of the fragments. This new methodology facilitates biological studies of ?-macroglobulins, and will enable elucidation of the role the C-terminal region may exert to eliminate ?-macroglobulin-proteinases complexes from the circulation by the LRP/receptor. © 2006 Elsevier Inc. All rights reserved.